A model discipline : political science and the logic of representations - Clarke, Kevin A.; Primo, David M. (Oxford : Oxford University Press, 2012)
Political scientists use models to investigate and illuminate causal mechanisms, generate comparative data, and more. But how do we justify and rationalize the method? Why test predictions from a deductive, and thus truth-preserving, system? Primo and Clarke tackle these central questions in this novel work of methodology.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Keywords: Political science -- Methodology